Infrastructure Multi-Layer Model for Smart Spaces Middleware Development - Sergey Marchenkov (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2018)
The most recent advances in Internet of Things (IoT) are aimed at the development of software platforms defined as middleware. A smart space makes fusion of the physical and information worlds enhancing a IoT environment by enabling information sharing for a variety of local digital devices and global resources from the Internet. The growing number of application smart spaces requires a middleware that provides opportunities for the development of context-aware applications based on multi-agent approach. The paper presents a perspective on how to design a software infrastructure of semantic-oriented middleware for smart spaces deployment in IoT environments. This paper introduces the middleware infrastructure multilayer model. The paper also involves an analysis of middleware requirements for development and deployment of smart spaces in IoT environments and the implementation of the requirements in the proposed model. As a reference case study the CuteSIB semantic information broker implementation of the Smart-M3 platform is considered.